2018
DOI: 10.14814/phy2.13637
|View full text |Cite
|
Sign up to set email alerts
|

Exercise mitigates the effects of hyperhomocysteinemia on adverse muscle remodeling

Abstract: Hyperhomocysteinemia (HHcy) is known for causing inflammation and vascular remodeling, particularly through production of reactive oxygen species (ROS) and matrix metalloproteinase‐9 (MMP‐9) activation. Although its effect on the skeletal muscle is unclear, HHcy can cause skeletal muscle weakness and functional impairment by induction of inflammatory mediators and macrophage mediated injury. Exercise has been shown to reduce homocysteine levels and therefore, could serve as a promising intervention for HHcy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(152 reference statements)
0
6
0
Order By: Relevance
“…We and others have shown that Hcy induces oxidative stress, which in turn induces MMPs in a variety of pathological conditions, both in vivo and in vitro settings [32,46,47]. Changes in MMPs expression and activity can lead to disproportional ECM synthesis and accumulation causing deleterious vascular remodelling [48,49].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We and others have shown that Hcy induces oxidative stress, which in turn induces MMPs in a variety of pathological conditions, both in vivo and in vitro settings [32,46,47]. Changes in MMPs expression and activity can lead to disproportional ECM synthesis and accumulation causing deleterious vascular remodelling [48,49].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…CBS is one of the key enzymes in the transsulfuration pathway, and heterozygous CBS deficiency (CBS+/À) has proved to be a useful model for analyzing the effects of mild to a severe endogenous elevation in the levels of Hcy (Familtseva et al 2014;Nandi and Mishra 2017;Narayanan et al 2013;Tyagi et al 2011Tyagi et al , 2012Watanabe et al 1995;Winchester et al 2018;Yang et al 2018). Hence, in this study, we used CBS +/À mouse model to dissect the effect(s) of HHcy on neoangiogenesis in the skeletal muscle and evaluate whether exogenous administration of GYY4137 (an H 2 S donor) could improve this effect(s).…”
Section: Introductionmentioning
confidence: 99%
“…HHcy is a known risk factor for vascular diseases (Ganguly and Alam 2015), however several studies also reported that HHcy leads to skeletal muscle weakness and functional impairment (Kalra et al 1985; Kanwar et al 1976; Veeranki et al 2014, 2015; Veeranki and Tyagi 2013, 2015a; Winchester et al 2018). Children born with severe homocystinuria due to CBS deficiency exhibit reduced body weight, skeletal muscle myopathy, and die in teenage years (Majumder et al 2017).…”
Section: Hyperhomocysteinemia-mediated Skeletal Muscle Pathophysiologymentioning
confidence: 99%
“…Children born with severe homocystinuria due to CBS deficiency exhibit reduced body weight, skeletal muscle myopathy, and die in teenage years (Majumder et al 2017). A clinical manifestation of HHcy displays decreased body mass and loss of skeletal muscle mass, which ultimately lead to myopathy (Kalra et al 1985; Kanwar et al 1976; Veeranki et al 2014; 2015; Veeranki and Tyagi 2013, 2015a; Winchester et al 2018). Results from our laboratory previously showed that HHcy mice (CBS +/− gene) have lower body mass and less fatigue resistance and produce less contractile force, have lower muscle ATP levels, low dystrophin, and mitochondrial transcription factor A (mtTFA) compared to control mice (C57BL/6J) (Veeranki and Tyagi 2015a).…”
Section: Hyperhomocysteinemia-mediated Skeletal Muscle Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation